Vascular conditioning prevents adverse left ventricular remodelling after acute myocardial infarction: a randomised remote conditioning study. (2nd May 2022) - Vlastos, D; Ikonomidis, I; Andreadou, I; Gazouli, M; Efentakis, P; Varoudi, M; Makavos, G; Kapelouzou, A; Lekakis, J; Parissis, J; Katsanos, S; Tsilivarakis, D; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): EU-CARDIOPROTECTION COST ACTION (European Cooperation in Science and Technology-Action) (CA16225) Background: Remote ischemic conditioning (RIC) alleviates ischemia-reperfusion injury via several pathways, including micro-RNAs (miRs) expression and oxidative stress modulation. Purpose: We investigated the effects of RIC on endothelial glycocalyx, arterial stiffness, LV remodelling, and the underlying mediators within the vasculature as a target for protection. Methods: We block-randomised 270 patients within 48 h of STEMI post-PCI to either one or two cycles of bilateral brachial cuff inflation, and a control group without RIC. We measured: (a) the perfusion boundary region (PBR) of the sublingual arterial microvessels to assess glycocalyx integrity and (b) the carotid-femoral pulse wave velocity (PWV) at baseline (T0), following every RIC cycle (T1, T2), and 40 min after RIC onset (T3); (c) miR-144, -150, -21, -208, nitrate-nitrite (NOx) and malondialdehyde (MDA) plasma levels at baseline (T0) and 40 min after RIC onset (T3); and (d) LV volumes at baseline and after one year. Results: Compared to baseline, there was a greater PBR and PWV decrease, miR-144 and NOx levels increase (p < 0.05) at T3 following single- than double-cycle inflation (PBR:ΔT0-T3 = 0.249 ± 0.033 vs 0.126 ± 0.034 μm, p = 0.03 and PWV:0.4 ± 0.21 vs -1.02 ± 0.24 m/s, p = 0.03). Increased miR-150, -21, -208 (p < 0.05) and reduced MDA was observed after both protocols. Increased miR-144 was related to PWV reduction (r = 0.763, p < 0.001) after the first-cycle inflation in both protocols. After one year, single-cycle RIC was associated with LV end-systolic volume reduction (LVESV) > 15% (odds-ratio of 3.75, p = 0.029). MiR-144 and PWV changes post-RIC were interrelated and associated with LVESV reduction at follow-up (r = 0.40 and 0.37, p < 0.05), in the single-cycle RIC. Conclusions: RIC evokes "vascular conditioning" likely by upregulation of cardio-protective microRNAs, NOx production, and oxidative stress reduction, facilitating reverse LV remodelling.